Language logic An Approach to the Sociology of Connected Discourse by Dr. Abd al-Ilah Ahmad (Journal of the College of Basic Education, 2022)
The approach intended to analyze a pioneering critical experience in the modern Iraqi academic and cultural scene, which is the experience of Dr. Formation of his style and language.